Incendiary Humor: Climate Change, Biodiversity, and Politics in Wildfire Cartoons. Issue 3 (3rd April 2022) - Moret-Soler, Diana; Mateu, Anna; Domínguez, Martí
ABSTRACT: Wildfires are part of the natural functioning of ecosystems, although anthropogenic factors such as climate change or land use are introducing important modifications in their natural regime. This text explores how cartoonists construct their discourse concerning an environmental subject of the importance of forest fires. Cartoons have proved to be a useful tool to illustrate changing attitudes, promote critical reflection, and mobilize action. Here, we study how cartoons portray and discuss wildfires in four regions especially affected by fires (Australia, California, Amazonia, and the Iberian Peninsula [Galicia and Portugal]) during a 4-year period (2017–2020). After an analysis of 468 cartoons, our results show that cartoon depictions focus on political and social issues related to wildfires, presenting them mainly from an anthropocentric point of view. Conversely, they leave aside issues such as their environmental impact, the loss of biodiversity, or the influence of climate change.